Galerkin Approach for the Study of Urea Concentration Distribution in Artificial Kidney in Hemodialysis - Gumanju, Mina; Gurung, Dil Bahadur (Journal of the Institute of Engineering, 2020)
Hemodialysis is the process of purifying the blood which removes the waste product such as urea from blood through the semi-permeable membrane of dialyzer. In dialyzer, the rate of blood flow velocity is maintained around five times less than the dialyzed flow velocity during hemodialysis. The study focuses on the urea concentration distribution in the blood during dialysis using partial differential equation of diffusion process developed by J. N. Kapur, assuming blood is Newtonian, and laminar flow. The solution of urea concentration is obtained using Galerkin approximation method associated with appropriate boundary conditions.